2015
DOI: 10.1007/s12035-015-9221-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hsp27 Rescued Neuronal Cell Death and Reduction in Life- and Health-Span in Drosophila melanogaster Against Prolonged Exposure to Dichlorvos

Abstract: Long-term exposure to dichlorvos (O,O-dimethyl-2,2-dichlorovinyl phosphate (DDVP), an organophosphate pesticide) is reported to exert neurotoxicity, i.e., generation of reactive oxygen species (ROS), oxidative damage, and neuronal cell death along with life- and health-span reduction in nontarget organisms including humans. However, studies on genetic modulation towards neuroprotection against prolonged DDVP exposure are elusive. Hsp27 (a small heat shock protein) is involved in various cellular processes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…HSP27 in atherosclerotic plaques diminishes with progression of the stage of the pathology [ 15 , 16 ] and is thereby viewed as a potential biomarker [ 14 ]. It has also been shown that HSP27 can protect cells from apoptosis induced by various stimuli in vivo and in vitro [ 17 20 ]. This cytoprotective effect of HSP27 is associated with decrease in ROS [ 21 ] and increase in glutathione [ 22 ] during oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…HSP27 in atherosclerotic plaques diminishes with progression of the stage of the pathology [ 15 , 16 ] and is thereby viewed as a potential biomarker [ 14 ]. It has also been shown that HSP27 can protect cells from apoptosis induced by various stimuli in vivo and in vitro [ 17 20 ]. This cytoprotective effect of HSP27 is associated with decrease in ROS [ 21 ] and increase in glutathione [ 22 ] during oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have shown that overexpression of Hsp27 in the brain ameliorates symptoms of neurological diseases. 17 29…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, Drosophila has been previously used to understand the link between Hsp27 , aging, and locomotory behavior. 17 The European Centre for the Validation of Alternative Methods (ECVAM) recommends Drosophila as an alternative model that follows the 3R rule, i.e., reducing, refining, and replacing the use of laboratory animals. 18…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand we found that basal as well as heat shock induced levels of Hsp27 were significantly more elevated in AR fed larvae. It is interesting that although Hsp27 is reported to be unessential for surviving heat shock (Hao et al 2007), it plays significant roles in tolerance to other insults like starvation, oxidative stress etc and also in determining the life span of flies (Hao et al 2007, Pandey et al 2015Shi et al 2011;Wang et al 2004). Thus, the improved thermo-tolerance of AR fed larvae and flies does not appear to be due to their stronger heat shock response.…”
Section: Discussionmentioning
confidence: 99%